2019
DOI: 10.1080/10715762.2019.1612891
|View full text |Cite|
|
Sign up to set email alerts
|

Biotin attenuation of oxidative stress, mitochondrial dysfunction, lipid metabolism alteration and 7β-hydroxycholesterol-induced cell death in 158N murine oligodendrocytes

Abstract: Lizard (2019) Biotin attenuation of oxidative stress, mitochondrial dysfunction, lipid metabolism alteration and 7β-hydroxycholesterol-induced cell death in 158N murine oligodendrocytes, Free Radical Research, 53:5, 535-561, ABSTRACT Mitochondrial dysfunction and oxidative stress are involved in neurodegenerative diseases associated with an enhancement of lipid peroxidation products such as 7b-hydroxycholesterol (7b-OHC). It is, therefore, important to study the ability of 7b-OHC to trigger mitochondrial defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 100 publications
4
28
0
Order By: Relevance
“…In additional, we detected the ROS by flow cytometry and found that GEP could decrease the expression of ROS, suggesting that apoptosis of ICCs was reduced by GEP on the basis of lowering the ROS. This point coincides with the previous study [37].…”
supporting
confidence: 94%
“…In additional, we detected the ROS by flow cytometry and found that GEP could decrease the expression of ROS, suggesting that apoptosis of ICCs was reduced by GEP on the basis of lowering the ROS. This point coincides with the previous study [37].…”
supporting
confidence: 94%
“…In 158N cells, anti-apoptotic and anti-oxidant capacities of natural or synthetic compounds and their ability to attenuate or to prevent toxicity of 7KC or 7β-OHC were often evaluated. In 158N cells incubated with 7KC or 7β-OHC, the cytoprotective effect of dimethylfumarate (DMF; Tecfidera) and biotin (vitamin B8), which are used for the treatment of MS, have been shown [120,121]. Natural products including argan oil, milk thistle seed oil, sea urchin egg oil, Carpobrotus edulis ethanol-water extract also strongly attenuate 7KC and/or 7β-OHC-induced cytotoxicity [121][122][123][124][125].…”
Section: -In Vitro Models Applied To the Study Of Neurodegenerative Diseases And The Identification Of Cytoprotective Compounds In This Fmentioning
confidence: 99%
“…The schematic signaling pathways presented in Figure 3 summarize the data obtained with 7β-OHC on cells from different types and species: promonocytic / monocytic human U937 / THP1 cells [25,47]; vascular cells (endothelial and smooth muscle cells) [25,148]; wild type human mammary tumor MCF-7 cells (caspase-3 deficient), and genetically modified MCF-7 (MCF-7/c3: stably transfected with caspase-3) [138], human retinal pigment epithelial cells (ARPE-19) [100] / primary porcine retinal epithelial cells; rat C6 glioblastoma cells [171], murine oligodendrocytes 158N and murine microglial BV-2 cells [3,114,119,121,141,142]. The different cells used permitted determination of the signaling pathways involved in 7β-OHC-induced cytotoxicity and to define the relationships between ROS overproduction, apoptosis, autophagy and inflammation.…”
Section: -7β-hydroxycholesterol-induced Oxiapoptophagy and Inflammation: Associated Signaling Pathwaymentioning
confidence: 99%
“…As shown in rat oligodendroglia, carboxylase activities are sensitive to levels of biotin availability [49]. Further, biotin can attenuate oxidative stress and mitochondrial dysfunction in murine oligodendrocytes [50].…”
Section: Plos Onementioning
confidence: 87%